Department of Genetics, University College of science, Osmania University, Hyderabad Telangana, India-500007. - Hemalatha Kamurthy; Mandan Tejmal; Pulak Majumder; HR Ambujakshi (International Journal of Phytomedicine, 2016)
The genus Candida is caused morbidity and mortality in human beings. The virulence factors of the Candida albicans have the great role in the pseudohyphae formation by attached with epithelial cells and endothelial cells. The aim of the study was to evaluate the antifungal activity of weed extracts used in traditional herbal medicine. The weeds were selected on the basis of their reported ethnobotanical uses. Water and alcoholic weed extracts were screened in vitro for their antifungal activity against fungus C. albicans. 50μl concentration of minimal Inhibitory Concentration (MIC) of Mimosa pudica extract in alcohol and 70μl concentration of MIC of Oxalis corniculata extract shows in alcohol. We conclude from this that these extracts exhibit amazing fungicidal properties that support their traditional uses. The presence of phytochemicals in the extracts including, tannins, alkaloids, steroids, glycosides, triterpenoids, flavonoids, phenolic compounds and organic acids like, Malic acid, tartaric acid and citric acid may be responsible for these activities. The acetone extracts of plant are more efficient as compared to the water extract.